2014
DOI: 10.4038/cmj.v45i4.6589
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of systemic lupus erythematosus in Sri Lankan patients: results from a lupus clinic

Abstract: Objectives To find the common clinical features, pattern of visceral involvement, treatment received and outcome in patients diagnosed as having systemic lupus erythe matosus (SLE) on American Rheumatological Association (ARA) criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
3
1
0
Order By: Relevance
“…74% were 20-40 years, with just over half belonging to the 21-30 year age group. These findings were comparable to studies done worldwide over the past ten years (1,4,5,9 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…74% were 20-40 years, with just over half belonging to the 21-30 year age group. These findings were comparable to studies done worldwide over the past ten years (1,4,5,9 ).…”
Section: Discussionsupporting
confidence: 91%
“…anti ds-DNA positivity was in concordance with similar studies reiterating the sensitivity of these markers in lupus nephritis (7,9). A neurological Paper Journal of Diagnostic Pathology 2014;9(2):14-22 disorder was found in a very small number of our patients, although it has been reported to be commoner in western studies (10,11).…”
Section: Discussionsupporting
confidence: 91%
“…5 Studies from Norway and Sri Lanka reported average age of 36 years and 32 years, respectively. 6,7 In our study, majority were females (85.42%) with male-to-female ratio 1:5.86. Thumboo et al, 8 Moss et al 9 and Estes and Christian 10 reported 93%, 92% and 91% female sex, respectively.…”
Section: Discussionsupporting
confidence: 48%
“…One observational study carried out in SL showed that 69% of patients developed renal involvements during a follow up of 3 years. The majority of them had focal or diffuse proliferative glomerulonephritis [ 6 ]. The current study aims to describe the clinicopathological findings, treatment response and predictors of long-term outcome of patients with WHO class III–IV LN in SL, managed according to the Euro-lupus regime.…”
Section: Introductionmentioning
confidence: 99%